2007
DOI: 10.1200/jco.2007.13.2191
|View full text |Cite
|
Sign up to set email alerts
|

Involved-Field Radiation Therapy for Inoperable Non–Small-Cell Lung Cancer

Abstract: The use of IFRT did not cause a significant amount of failure in lymph node regions not included in the tumor volume. Therefore, IFRT remains an acceptable method of treatment that allows for dose escalation while minimizing toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(84 citation statements)
references
References 25 publications
1
81
1
1
Order By: Relevance
“…Involved-field radiation to high dose without elective nodal irradiation has been shown to allow a higher dose of radiation with acceptable toxicity and low risk for isolated nodal relapse. 115,116,[125][126][127][128] It is essential to evaluate the dose-volume histogram of critical structures and to limit the doses to the spinal cord, lungs, heart, esophagus, and brachial plexus to minimize normal tissue toxicity (see Table 3 on page 762). These limits are largely empiric.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Involved-field radiation to high dose without elective nodal irradiation has been shown to allow a higher dose of radiation with acceptable toxicity and low risk for isolated nodal relapse. 115,116,[125][126][127][128] It is essential to evaluate the dose-volume histogram of critical structures and to limit the doses to the spinal cord, lungs, heart, esophagus, and brachial plexus to minimize normal tissue toxicity (see Table 3 on page 762). These limits are largely empiric.…”
Section: Radiation Therapymentioning
confidence: 99%
“…• When conformal techniques are utilized and the treating physician has performed a comprehensive evaluation of disease involvement, an involved fi eld approach is used for target volume delineation in NSCLC, due to the published low likelihood of disease recurrence in elective lymph nodes (Rosenzweig et al 2001(Rosenzweig et al , 2007 ). An involved fi eld technique plus inclusion of the ipsilateral hilum is also now recommended in the Radiation Therapy Oncology Group's (RTOG's) recent randomized trial examining the effect of dose on survival (RTOG 0538).…”
Section: Target Volume Delineation and Treatment Planningmentioning
confidence: 99%
“…They concluded that the incidence of nodal failure was low and did not seem to be due to high-dose incidental irradiation. Rosenzweig et al reported the results of IF-RT in a large number (524) of patients with stage I-III (65% stage III) NSCLC 8) . Only 32 patients (6.2%), 42 nodal regions with ENF were identified, and among the 42 nodal regions, six regional failures (14%) were in nodal regions that had incidentally received >45Gy, which is a typical dose of ENI.…”
Section: Incidental Irradiation Of If-rtmentioning
confidence: 99%
“…The argument against the use of ENI may be summarized as follows 6,7) . 1) Failure is uncommon in nodal regions that are neither clinically involved nor specially targeted from many reports [8][9][10][11][12] .…”
Section: The Evidence Of If-rt -Is Eni Needed?mentioning
confidence: 99%